[11C]-WAY100635 PET demonstrates marked 5-HT1A receptor changes in sporadic ALS. - Turner, M; Rabiner, E; Hammers, A; Al-Chalabi, A; Grasby, P; Shaw, C; Brooks, D; Leigh, P (2005)
The pathogenesis of amyotrophic lateral sclerosis (ALS) remains obscure, but it is now clear that neuronal loss is not confined to the motor cortex, even in cases without dementia. A reliable method of assessing cortical involvement in vivo remains elusive. WAY100635 binds selectively to the 5-hydroxytryptamine (5-HT1A) receptor, which is expressed on pyramidal neurones present throughout the cortex. [11C]-WAY100635 PET is, therefore, a potential marker of cerebral neuronal loss or dysfunction in ALS. Twenty-one ALS subjects and 19 healthy volunteers underwent [11C]-WAY100635 PET of the brain. A cortical template consisting of multiple volumes of interest (VOI) was applied to each individual's [11C]-WAY100635 binding potential (BP) image to determine the regional reduction in binding in ALS patients compared to controls. There was a marked reduction (21%) in both the global cortical and raphe BP of [11C]-WAY100635 in ALS patients (P < 0.001), with regional variations in the VOI analysis that ranged from 16% to 29% decrease compared with the control group, and trends to greater reductions in those with bulbar involvement. To clarify the significance of the global cortical reductions, statistical parametric mapping was used as an alternative method to identify the cortical regions with the most significant decreases in [11C]-WAY100635 binding. SPM analysis revealed the greatest differences between ALS cases and controls in frontotemporal regions, cingulate and lateral precentral gyri. The reductions in cortical [11C]-WAY100635 binding were not related to depression, riluzole or other drug use. We postulate that the reduction of 5-HT1A binding represents loss of, or damage to, neurones bearing these receptors although we cannot exclude the possibility that these reductions reflect alterations in receptor expression or function. Further investigation into the role of the 5-HT1A receptor and the potential of [11C]-WAY100635 PET as a marker of cortical dysfunction in ALS is warranted.